Frontispiece: Boron–Ligand Cooperation: The Concept and Applications. Issue 18 (27th March 2021) - Hasenbeck, Max; Gellrich, Urs
Abstract : Boron–ligand cooperation describes a specific mode of action by which certain metal‐free systems activate chemical bonds. In this process, a covalently bound substituent at the boron is actively involved in the bond activation process and changes to a datively bound ligand in the course of the bond activation. The evolution of the term boron–ligand cooperation as well as examples of bond activation by boron–ligand cooperation are discussed in the Minireview by M. Hasenbeck and U. Gellrich on page 5615 .